Current human rights problems: new paradigms in a context of global changes - Fariñas Dulce, María José (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
The journal “Derechos y Libertades” invites us to provide our opinion on the challenges currently facing the discourse on human rights. The question posed leads us to consider the historical context of the very concept of human rights, which cannot be grounded solely on abstract reasoning but rather onan evolving, diverse, and intercultural understanding of both humanity and society. Challenges to this concept have always existed and are multifaceted, yet perhaps now we find ourselves at a moment characterized by significant technological advancements and energy transitions. This situation calls for anethical, political, and juridical approach to address the emerging social conflicts resulting from their application.
Keywords: paradigm; systemic crisis; artificial intelligence; globalization; social justice; neoliberalism; democracy; human rights